Akuntabilitas dan Transparansi Pengelolaan Dana Punia Di Pura Dalem Kangin, Desa Pakraman Banyuning, Kecamatan Buleleng - Luh Ari Meiningsih; Anantawikrama Tungga Atmadja (Universitas Pendidikan Ganesha, 2021)
Bali is known to have a diversity of cultures, one of which is culture in giving gifts, the basis of this teaching is sincere in accordance with the teachings of the Dharma. Desa Pakraman is a non-governmental public institution, everything managed in it must be based on the principles of accountability and transparency. Likewise with the temple in Pakraman village, and is already an organization. In managing any finance must be in accordance with the principle of accountability. One of them is financial management in the ounia fund system in Pura Dalem Kangin, Pakraman Banyuning Village. To understand accountability and transparency in the management of punia funds in Pura Dalem Kangin, Pakraman Banyuning Village, Buleleng Subdistrict, this study aims to find out (1) How to manage financials in the Pura Dalem Kangin fund system, Desa Pakraman Banyuning and (2) How do the punia fund manager understands the principles of accountability in the management of collected funds This research was conducted with qualitative methods that focus more on the description of the study. Data obtained through in-depth interviews, observation, documentation studies of informants who have knowledge in their fields. Furthermore, this data is processed through three stages, namely (1) Reduction, (2) Presentation, and (3) Conclusion Withdrawal. The results of this study indicate that (1) the punia fund management system is pretended to miss using a simple management system with a clearly understood flow that is carried out directly by the administrators therein (2) the managers have understood very well the principles of accountability that consist of transparency , obligations, controls and responsibilities